Perancangan Aplikasi Keamanan Bank Soal Ujian Sekolah Menggunakan Algoritma Kriptografi Elgamal Berbasis Web - Haibah, Mahmubin; Riza, Ferdy (Lembaga Riset Mutiara Akbar, 2025)
Data security is a crucial aspect of the education system, particularly in the management of school exam question banks. Leakage of exam questions can compromise the integrity of the evaluation process and affect the credibility of educational institutions. To address this challenge, this study designs a web-based application for securing exam question banks by implementing the ElGamal cryptographic algorithm. This algorithm is chosen for its ability to maintain data confidentiality through encryption and decryption processes, as well as its use of distinct public and private keys. The application allows users or teachers to upload exam questions in PDF format, which are then encrypted using the ElGamal algorithm, ensuring that only those with the private key can access the contents. Testing was conducted to ensure that the application's functionalities work properly, from the upload process, encryption, file and private key storage, to the decryption of the exam file. The implementation results show that the system effectively secures exam questions and can be easily accessed by authorized users. With this system, the distribution and storage of exam questions are expected to be more secure, efficient, and confidential.